Generalized Ramsey interferometry explored with a single nuclear spin qudit. (December 2018) - Godfrin, Clément; Ballou, Rafik; Bonet, Edgar; Ruben, Mario; Klyatskaya, Svetlana; Wernsdorfer, Wolfgang; Balestro, Franck
Abstract Qudits, with their state space of dimensiond > 2, open fascinating experimental prospects. The quantum properties of their states provide new potentialities for quantum information, quantum contextuality, expressions of geometric phases, facets of quantum entanglement and many other foundational aspects of the quantum world that are unapproachable via qubits. Here, we have experimentally investigated the quantum dynamics of a qudit (d = 4) that consists of a single 3/2 nuclear spin embedded in a molecular magnet transistor geometry, coherently driven by a microwave electric field. In order to demonstrate the potentialities of molecular magnets for quantum technologies, we implemented three protocols based on a generalization of the Ramsey interferometry to a multilevel system. First, the Ramsey interference is used to measure the accumulation of geometric phases. Then, two distinct transitions of the nuclear spin are addressed to measure the phase of an iSWAP quantum gate. Finally, through a succession of two Hadamard gates, the coherence time of a 3-state superposition is measured. Quantum computing: controlling a qudit in a molecule The nucleus of a single atom in a molecule can be controlled with sufficient precision that multilevel interferometric protocols can be performed on it. A group of researchers from France and Germany, led by Wolfgang Wernsdorfer from Karlsruhe Institute of Technology, showed how to control the state of a nuclear spin of an atom inside a molecule placed inside a special transistor. The nucleus they use is a multilevel quantum system, which makes it more versatile than the more "mainstream" two-level systems (qubits). They generalise to the multilevel case one of the key primitives of quantum information processing, i.e., Ramsey interferometry, which allows to characterise the coherence time of quantum systems.